Functional Photochromic Methylhydrosiloxane‐Based Side‐Chain Liquid‐Crystalline Polymers. Issue 8 (24th March 2014) - Tóth‐Katona, Tibor; Cigl, Martin; Fodor‐Csorba, Katalin; Hamplová, Věra; Jánossy, István; Kašpar, Miroslav; Vojtylová, Terezia; Hampl, František; Bubnov, Alexej
<x xml:space="preserve">Abstract</x> A new azobenzene‐group‐containing monomer and several respective functional side‐chain polymers grafted on a methylhydrosiloxane backbone (with two different degrees of polymerization; with and without the addition of a photoreactive benzophenone derivative) are designed, synthesized, and characterized. The resulting materials clearly show self‐assembly behavior and possess a nematic liquid‐crystal phase over a broad temperature range, which extends below 0 °C. The optical properties of these new photochromic liquid‐crystalline materials are determined from the absorbance spectra of oriented samples and by photoinduced birefringence studies. The results indicate a considerable dichroism of the side‐chain liquid‐crystalline polymers (SCLCPs), and hence demonstrate their potential applicability for optical storage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>